1970
DOI: 10.3329/jbau.v7i2.4732
|View full text |Cite
|
Sign up to set email alerts
|

Effect of urea super granules, prilled urea and poultry manure on the yield of transplant Aman rice varieties

Abstract: An experiment was carried out at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh in transplant Aman season 2008 to find out the effect of urea super granules (USG), prilled urea (PU) and poultry manure (PM) on the yield and yield attributes of transplant Aman rice varieties. Two transplant Aman rice varieties viz. BRRI dhan41 and BRRI dhan46 and ten levels of integrated nutrient management encompassing USG, PU and PM were tested following randomized complete block design with thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
3
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 2 publications
1
4
3
2
Order By: Relevance
“…gave the lowest result on all the yield and yield contributing parameters. Similar result also reported by Kabir et al (2009). In a column, figures with same letter or without letter do not differ significantly whereas figures with dissimilar letter differ significantly (as per DMRT).…”
Section: Effect Of Nutrient Managementsupporting
confidence: 87%
See 1 more Smart Citation
“…gave the lowest result on all the yield and yield contributing parameters. Similar result also reported by Kabir et al (2009). In a column, figures with same letter or without letter do not differ significantly whereas figures with dissimilar letter differ significantly (as per DMRT).…”
Section: Effect Of Nutrient Managementsupporting
confidence: 87%
“…Among the management practices, application of poultry manure, nitrogen fertilizer and variety are the important ones. Kabir et al (2009) reported that a considerable portion (31.25%) of PU nitrogen saved by using USG (1.8g) together with other inorganic fertilizers or with PM at 2.5 t ha -1 . Hasan et al (2004) also stated that BRRI dhan34 fertilized with 75% NPKS + poultry manure at 5 t ha -1 produced the highest grain yield than Kalizira.…”
Section: Introductionmentioning
confidence: 99%
“…Third, estimated effects on the quantity of USG used by farmers in treatment villages show that the discount is only profitable for the fertilizer company if their production costs are roughly a quarter of the non-discounted selling price. Finally, although using USG is associated with higher rice yields in our data and the agronomy literature finds large gains in rice yields attributable to USG (Lupin et al, 1983;Thomas and Prasad, 1987;Ahmed et al, 2000;Jena et al, 2003;Kabir et al, 2009;Islam et al, 2012), we are unable to reject a null effect of either treatment on rice yields. This may be due to the observation that some farmers substitute away from both prilled urea and NPK (a complementary technology including nitrogen, phosphorous, and potassium) and that farmers in treatment villages are not more likely than farmers in control villages to adopt recommended practices associated with the optimal use of USG.…”
Section: Introductioncontrasting
confidence: 85%
“…Second, we add to the literature finding differences in estimated yield gains between agronomic trials and farmers using the same inputs under real-life conditions (Dar et al, 2013;Abate et al, 2018;Haile et al, 2017;Laajaj et al, 2020;Paul, 2021). The agronomic literature is clear that USG and the urea deep placement technology lead to increased rice yields (Lupin et al, 1983;Thomas and Prasad, 1987;Ahmed et al, 2000;Dobermann, 2005;Jena et al, 2003;Kabir et al, 2009;Islam et al, 2012). In our study, despite the observation that the use of USG is associated with higher rice yields compared to the use of prilled urea, we find that rice farmers in treatment villages do not realize any increase in rice yields.…”
Section: Introductioncontrasting
confidence: 71%
“…Poul et al, 2019 from Bangladesh observed highest grain yield with combined application of PM@2.5 t/ha with 75% RDF (Urea, TSP, MOP, Gypsum, ZnSO4 @ 250, 120, 120, 100, 10kg/ha respectively) in aromatic Boro rice (BRRI dhan 50). Kabir et al, 2009 [28] from Bangladesh observed that similar yield was obtained in Aman rice with the application of PM @ 2.5 t/ha in combination with full dose of Urea super granule (USG: 1.8g) or with full dose of prilled urea (PU) when compared with the yield obtained from full dose of USD (1.8g) and other inorganic fertilizers. Biswas et al, 2016 [12] from Bangladesh suggested that combined application of PM@5 t/ha with urea super granule 2.2g and prilled urea (115kg N/ha) produced significantly highest yield in scented rice (BRRI dhan 50).…”
Section: Effect Of Organic Nutrients On Yield Of Aromatic Ricementioning
confidence: 85%